A study of endothelial function by flow-mediated vasodilatation in patients with metabolic syndrome - Shubha Vishnu Hegde; Diwakar Tumkur Narsimhamurthy (Wolters Kluwer Medknow Publications, 2020)
Background: Metabolic syndrome (MetS) is characterized by clustering of cardiovascular risk factors.Endothelial dysfunction is the key early event in atherogenesis that occurs long before structural atherosclerotic changes and promotes cardiovascular events. The assessment of endothelial function by flow-mediated dilation (FMD) of the brachial artery has been proposed as a non-invasive marker for cardiovascular risk. Aim: Assessment of flow mediated vasodilatation of brachial artery as a non invasive marker of endothelial function in metabolic syndrome and To assess the relationship of number of risk factors in metabolic syndrome with endothelial dysfunction. Methodology: A case control study in which 50 patients with Metabolic Syndrome as per new IDF criteria and 50 controls were studied. Detailed clinical history, examination and Blood investigations like Fasting blood glucose, fasting lipid profile and ECG was done for every patients. Endothelial function was assessed by brachial artery flow mediated vasodilatation. Results: In the present study 100 (50 cases and 50 controls) patients were studied, males (54%) and females (46%), majority in the age group between 40-60 years (mean age - 49.76 ± 13.76yrs in cases and 44.94 ± 16.09 years among controls). We identified a significant difference between cases and age- and sex-matched controls regarding brachial artery FMD% (7.24 ± 5.24 and 21.29 ± 9.29 respectively; P value-0.000). Negative corelations were found between FMD% and various variables and also between number of components and FMD% (r = -0.239). Conclusion: MetS is associated with endothelial dysfunction as evidenced by decreased FMD% compared to controls. There is a negative correlation between various components of MetS, number of components of MetS and FMD%.